Organizational Citizenship Behaviour (OCB) towards Organizational Performance in the Hospitality Industry - Rasmulia Sembiring; Sunday Ade Sitorus (Dinasti Publisher, 2023)
The purpose of this study is to determine the pattern of determinants of tourism development for MSMEs in Indonesia which includes creative and innovative product variables, creative promotions and creative thinking patterns so that they have an impact on the variables of MSME development and MSME productivity. In this study, it is related to the development of MSME tourism, through the independent variables, namely creative and innovative products, creative promotions and creative thinking patterns, while the dependent variable is MSME development, and the moderating variable is MSME productivity. In this study the independent variable is related to MSME tourism development, such as creative and innovative product variables, creative promotion and creative mindset, the dependent variable is MSME development, with moderating variable MSME productivity. Through the results of research that has been stated that in order to increase the development of MSMEs and the productivity of MSMEs, MSMEs in the tourism industry are required to always increase the production of innovative and creative products, by developing a creative mindset, so that the business being pioneered can develop and be productive and generate profits that are profitable.